The Evolution of the System of Long and Short Adjectives in Old Russian - Larsen, Karin (Slavistische Beitraege, 2005)
The present study is a comprehensive analysis of the evolution of the system of long and short adjectives in Old Russian, a profound language change to which very little previous research has been devoted. It is generally assumed that in prehistoric Slavic, the system was purely grammatical with the long form denoting definiteness and the short form denoting indefiniteness. The present study finds, on the basis of evidence collected from Old Russian chronicle texts, that even the earliest of these sources display a substantially transformed system no longer reflecting the opposition between definiteness and indefiniteness, but governed by parameters of information structure.